How Can Stress Be Controlled in Endodontically Treated Teeth? A 3D Finite Element Analysis - İhsan Yıkılgan; Oya Bala (The Scientific World Journal)
The aim of this study was to analyze the stresses that develop by oblique and vertical forces in endodontically treated maxillary second premolars that were restored with resin composite. Additionally, in our study the effects of the different restorative approaches and use of different base materials on stress formation were analyzed using three-dimensional finite element stress analysis. For restoration, the models representing both cusp capping, palatinal cusp capping, standard MOD restoration, and use of woven fiber in occlusal part were prepared. In all models, oblique forces caused more stress than did vertical forces. Materials with low elastic moduli cause high amounts of stress, whereas materials with elastic moduli similar to that of dental tissues cause low amounts of stress. Additional approaches such as cusp capping, functional cusp capping, and woven fiber use do not affect stress formation on the tooth after endodontic treatment.